Continuous-flow catalytic deuterodehalogenation carried out in propylene carbonate - Orsy György; Fülöp Ferenc; Mándity István (2019)
A selective continuous-flow (CF) deuterodehalogenation approach is described performed in propylene carbonate, which is considered as one of the greenest solvents. Various CF technologies are known for hydrodehalogenation reactions; however, they are not directly transferable for deuteration transformations. A novel spherical activated carbon-supported palladium catalyst has been found to be useful for the catalytic deuterodehalogenation of haloarenes. After careful reaction parameter optimization, complete conversion was achieved for bromine-and chlorine-substituted haloarenes. Nonetheless, no deuterium exchange was observed for the fluorine substituent, while iodine-substituted compounds poisoned the catalyst. Importantly, deuterated compounds were obtained with a rate of 3 mg min-1 and the catalyst showed reasonable reusability. Moreover, benzylic amides were also deuterated without any debenzylation side-reaction.